1993
DOI: 10.1093/ajcn/57.3.399
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of lactose maldigestion, lactose intolerance, and milk intolerance

Abstract: Lactose digestion and tolerance were evaluated in 164 African Americans ranging in age from 12 to 40 y who claimed intolerance to one cup (240 mL) or less of milk. With use of a breath-hydrogen test with 25 g lactose as test dose and the presence or absence of symptoms, 50% of the subjects were classified as lactose maldigesters and intolerant, 8% were maldigesters but tolerant, 15% were digesters but intolerant, and 27% were digesters and tolerant. Forty-five subjects from the lactose maldigesting and intoler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 21 publications
2
45
0
3
Order By: Relevance
“…This is in line with other studies [6,8,9] showing that not all individuals with lactose malabsorption report symptoms from food containing lactose. T he colonic micro biota is variable [28] and the individual sensitivity to feel distension of the colon and to sense discomfort varies [29] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in line with other studies [6,8,9] showing that not all individuals with lactose malabsorption report symptoms from food containing lactose. T he colonic micro biota is variable [28] and the individual sensitivity to feel distension of the colon and to sense discomfort varies [29] .…”
Section: Discussionsupporting
confidence: 93%
“…celiac disease [3] . Cases of individuals suspecting they have lactose intolerance are more common than the true prevalence of adult-type hypolactasia [4][5][6][7][8][9] . It has been shown that lactose-restricted diets improve symptoms markedly for example in IBS patients with lactose malabsorption and reduce the number of visits to the outpatient clinics [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, lactose cannot be the reason for the increased symptoms. Similarly, several well-controlled studies have demonstrated that gastrointestinal symptoms after milk intake quite often occur independently of lactose intake (Rosado et al, 1987;Johnson et al, 1993;Vesa et al, 1996). It has been suggested that milk hypersensitivity in adults, which may be more common than previously thought, may cause gastrointestinal symptoms after milk intake (Pelto et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Elimination of lactose intolerance (3-70% depending on the populational group [1]), encouraging the utilization of lactose as an energy source, as well as calcium and magnesium assimilation from milk. 2.…”
Section: Introductionmentioning
confidence: 99%